Aristotle Language Learning Centre / Ahmad Fariz Nicholas ... [et al.] - Nicholas, Ahmad Fariz; Binit, Effaniza; Puasah, Faziella; Abdul Rasah, Mohd Nasir; Taip, Noor Isah (2011)
Aristotle Language Learning Centre (ALLC) is the proposed name of our business. This business focusing on service, which is, we provide our expert in language to teach the clients (students). In early operation, ALLC will be providing Chinese dialects, Japanese, and Korean intensive language course, which we aim to provide more languages options in future. These language courses will be teaching by experienced language teachers and lecturers, which will be completed in three month according to module I, module II, and module III for month 1, month 2, and month 3. We serve time flexibility to the student, which is; they can choose either to attend morning, afternoon, or evening session of these courses. This business will be run at Menara MBF, Gaya Street, Kota Kinabalu, Sabah (refer to section 6.0) at January 20t h , 2011. Nearby this building are the Sabah Tourism Board, banks, Kota Kinabalu Commercial College, and the new shopping complex, Suria Sabah. It is also nearby the main road, which connected Kota Kinabalu town to Likas, and Sepangar. In term of business prospect, according to Education Ministry Director general Tan Sri Alimuddin Mohd Dom, Ministry of Education has been planning to add third language subject in more secondary school. Related closely to this, parents will have the option to send their children to extra classes in order to get more exposure so that their children can master the language well. Hence, the existence of this business will provide more options to parents in term of giving the extra classes for their children.